Constraints and trade-offs for the next government - Carl Emmerson; Christine Farquharson; Paul Johnson; Ben Zaranko (Institute for Fiscal Studies (IFS), 2024)
The UK finds itself in an unfortunate economic and fiscal bind. Living standards have endured an unprecedentedly long stagnation. Taxes are at record levels for the UK (though remain lowto-middling by European standards). Public services are showing visible signs of strain and are, in many cases, performing less well than they were in 2010. Further tax rises and further cuts for most public services are built into current plans. But on official forecasts, this is only just enough to stabilise government debt as a fraction of national income.
Keywords: 330; Government finances and spending; Election 2024; Environment; Government spending; Higher education; Housing; Investment; Living standards; Public sector; Public finance; Social care; Tax; Working age benefits